DAMPAK PAJAK TANGGUHAN TERHADAP PERSISTENSI LABA: Studi Kasus pada Perusahaan Go- Publik di Indonesia Tahun 2020 - 2023 - Andhika Iman Wafi; Endang Kiswara (Diponegoro Journal of Accounting, 2025)
This study was conducted to examine the effect of deferred taxes on earnings quality as measured by Net Income (NI) and Operating Cash Flow (OCF) in Indonesian public companies during the period 2020-2023, incorporating the control variables Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Investment (ROI), and Cash Effective Tax Rate (CETR). The independent variable used is deferred taxes, while profit quality as the dependent variable is measured using two proxies, namely Net Income (NI) and Operating Cash Flow (OCF). This study uses secondary data in the form of financial statements of companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023 and a case study approach. Panel data regression analysis was applied using EViews 13 software to identify the effect of deferred taxes and control variables on profit quality. The results indicate that deferred taxes significantly influence profit quality, as measured by Net Income (NI) and Operating Cash Flow (OCF). Control variables such as DER, ROA, ROI, and CETR are also considered to provide a more comprehensive understanding of the factors affecting profit quality. These findings emphasize the importance of companies considering the impact of deferred taxes in preparing financial statements to enhance the quality of reported profits.